2019
DOI: 10.1155/2019/8285351
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic Assessment with Three-Dimensional Mode of the Urethral Compression Effect following Sling Surgery with and without Mesh Surgery

Abstract: Background The aim of this study was to assess anatomical changes in the urethra at rest and during straining following sling surgery with and without transvaginal mesh surgery (TVM) in women with stress urinary incontinence (SUI) with or without pelvic organ prolapse (POP) using three-dimensional ultrasonography. Methods 76 women with SUI with or without pelvic organ prolapse after sling surgery. They underwent sling surgery alone (S group, n=36) or concomitant TVM (M group, n=40). All patients underwent urin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…Instead, the value of ultrasound is in the assessment of bladder-neck movement while increasing abdominal pressure in women with USI. By the same token, we previously reported the changes in bladder-neck mobility following hysterectomy, antiincontinence surgery, and vaginal laser therapy using TPUS [20][21][22][23][24][25]. Our previous study showed assessed the efficacy on noninvasive erbium-doped yttrium aluminum garnet laser (Er:YAG laser) for female SUI.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, the value of ultrasound is in the assessment of bladder-neck movement while increasing abdominal pressure in women with USI. By the same token, we previously reported the changes in bladder-neck mobility following hysterectomy, antiincontinence surgery, and vaginal laser therapy using TPUS [20][21][22][23][24][25]. Our previous study showed assessed the efficacy on noninvasive erbium-doped yttrium aluminum garnet laser (Er:YAG laser) for female SUI.…”
Section: Discussionmentioning
confidence: 99%